Dieulafoy lesion: two pediatric case reports - Giovanni Di Nardo; Gianluca Esposito; Angela Mauro; Letizia Zenzeri; Gian Paolo Ciccarelli; Andrea Catzola; Alessandro Rossi; Vito Domenico Corleto (BMC, 2020)
Abstract Background Massive gastrointestinal bleeding in children is uncommon. Dieulafoy lesion is an uncommon disease which may lead to massive and repeated upper gastrointestinal hemorrhage. We report two cases of gastric Dieulafoy lesion successfully treated with either band ligation or endoscopic hemoclipping. Case presentation First case report: A previously healthy 18-month-old female infant with E. coli sepsis, pneumonia and respiratory failure with bilateral pneumothorax requiring chest drainage. Over a few days, the patient presented hematemesis and melena with progressively worsening anemia. The esophagogastroduodenoscopy revealed an arterial vessel with eroded apex located between the body and the fundus of the stomach. Two elastic bands were applied which resulted in resolution of hematemesis and melena and improvement of the anemia. Second case report: A 8-year-old male was admitted to our department with sudden massive hematemesis and melena. Clinical examination revealed anemia (hemoglobin, 6.8 g/dl). Esophagogastroduodenoscopy revealed a mucosal erosion with visible vessel located along the small curvature, close to the antrum. Three hemostatic clips were placed on the Dieulafoy lesion and hemostasis was obtained. Conclusions we showed that, similar to gastric DL in adult patients,, gastric DL in pediatric patients can be successfully treated with endoscopic therapy, and both hemoclipping and band ligation are suitable techniques.